Factors affecting pollution referenda - Abt Associates; United States. (Environmental Protection Agency, 1971)
Many local governments wanting to finance construction of water pollution control facilities through the sale of municipal bonds are required to obtain authorization from the electorate in the form of a bond referendum. Since defeat of such a bond issue can result in significant delay in implementation of the Federal Water Pollution Control Act, it is important that EPA understand the factors which affect the outcome of these elections. The study contains conclusions and recommendations about the process by which the project is planned, the role of the bond market, and the referendum as an approval mechanism for public expenditures
Publisher location came from U.S. EPA About EPA, Mailing addresses and phone numbers webpage
EPA report number EPA 16110-EXW-0671, per NSCEP's publication title list
"This report was submitted in fulfillment of Contract Number 14-12-902 under the sponsorship of the Water Quality Office, Environmental Protection Agency."--Page iii
"June 1971"--Title page
"Project # 16110 EXW Contract # 14-12-902"--Title page
Keywords: Sewage disposal / Finance. / fast / (OCoLC)fst01113879; Referendum. / fast / (OCoLC)fst01092465; Municipal bonds. / fast / (OCoLC)fst01029183; Sewage disposal / United States / Finance; Referendum / United States; Municipal bonds / United States; United States. / fast / (OCoLC)fst01204155